Analisis Perencanaan dan Ketersediaan Obat di Kabupaten dan Kota Provinsi Jawa Timur - Digdo Suryagama; Satibi Satibi; Sumarni Sumarni (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
The problem of drug availability always occurs in District/Municipality every year. Research related to drug management, especially those related to the evaluation of drug availability and the value of damaged/expired drugs, has been carried out in the last ten years. Almost all the research found problems with the availability of the drugs. The Director General of Pharmacy and Medical Devices reported that the percentage of the availability of National Medicines in East Java in 2017 had reached 96.55%, but had not yet described the condition of the availability of medicines in real terms because the calculation did not use data on drug quantity. This study aims to explain the real conditions for the availability of 17 items of national indicator drugs in East Java in 2017, as well as identify problems and information about management that has been running in 2017. This research is an observational research that is descriptive quantitative. The research instrument was in the form of data collection sheets for the availability of 17 drug items in 2017 and interview guidelines. The results showed that the availability of drugs was in excess conditions with an average of 22.5 months. Drug programs held directly by the Central Government often experience excess inventory at the Regency/City Pharmacy Department level but the average percentage of drugs damaged/expired is still in a fairly good range (0-3%). It can be concluded that the availability of drugs in East Java Province in 2017 is influenced by the planning system, procurement system, availability of drugs at the provider level (supply), availability of management information systems and respective regional policies.